The connection between climate change and perinatal mental health - Barkin, Jennifer L.; van Rhijn, Sanne; Johnson, Chloe M. (Frontiers in Psychiatry, 2025)
Climate change and extreme weather events are particularly concerning for pregnant and postpartum women and have been related to negative birth outcomes. However, the impact of climate change on perinatal mental health outcomes is not well studied. Mood and anxiety disorders are among the leading comorbidities during pregnancy and the postpartum period, and they are associated with significant familial and societal burdens. It is crucial to include environmental factors in the risk profile of perinatal mental illness to optimize prevention and early intervention strategies. In the clinical experience of one of the authors, new mothers can feel particularly concerned about their baby’s physical health when faced with extreme heat or may present as agitated due to heat-related sleep deprivation. This is in line with qualitative research showing maternal worrying about a baby’s thermal dysregulation as one of the emerging themes. With extreme weather events becoming more frequent, clinicians have a role in advocating for climate adaptation in healthcare settings. Climate inequalities need to be addressed alongside health and social inequalities.